MODERN PERSPECTIVES IN BULGARIAN ENGINEERING EDUCATION THROUGH THE PRISM OF EXPERTS FROM THE IT SECTOR (EMPIRICAL STUDY) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
We are witnessing a confluence of technology, information, communication and artificial intelligence that emphasizes the importance of soft skills, communication skills, critical thinking, problem solving, teamwork in engineering. This, in turn, necessitates an emphasis on interdisciplinary training by educational institutions in the preparation of engineering personnel, in accordance with the requirements of business in the IT field. The research was conducted on the territory of the city of Sofia in the Republic of Bulgaria, where a significant number of small and medium-sized IT companies are positioned with opportunities to hire graduating students and accordingly, the experts working in them to assess their competences, but also to assess the requirements of those for training of engineering staff from universities in the IT sector. From this point of view the purpose of the publication is to establish from a certain group of respondents some modern perspectives in Bulgarian engineering education from the point of view of business representatives. Based on the purpose of the study a questionnaire was drawn up and sent to respondents to assess what knowledge and skills future IT engineers should possess. This necessitated the use of a quantitative approach through an online survey that was randomly sent to 24 small and medium-sized IT enterprises. The completed and returned surveys are from 59 experts, representatives of 16 enterprises. The research showed that IT business experts need IT engineering personnel who have not only narrowly specialized knowledge in the relevant professional field, but also interdisciplinary ones with a wide range of work and decision-making skills.